1996
DOI: 10.1007/bf00328447
|View full text |Cite
|
Sign up to set email alerts
|

Host adaptation in the anther smut fungus Ustilago violacea (Microbotryum violaceum): infection success, spore production and alteration of floral traits on two host species and their F1-hybrid

Abstract: It is often assumed that host specialization is promoted by trade-offs in the performance of parasites on different host species, but experimental evidence for such trade-offs is scant. We studied differences in performance among strains of the anther smut fungus Ustilago violacea from two closely related host plant species, Silene alba and S. dioica, on progeny of (1) the host species from which they originated, (2) the alternative host species, and (3) inter-specific hybrids. Significant intra-specific varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 45 publications
6
65
1
Order By: Relevance
“…This is in agreement with previous studies showing strong differentiation between host races of M. violaceum, which might be considered as different species (Biere and Honders, 1996;Shykoff et al, 1999;Bucheli et al, 2000). Among amplifiable microsatellites, only 6.7% were polymorphic.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with previous studies showing strong differentiation between host races of M. violaceum, which might be considered as different species (Biere and Honders, 1996;Shykoff et al, 1999;Bucheli et al, 2000). Among amplifiable microsatellites, only 6.7% were polymorphic.…”
Section: Discussionsupporting
confidence: 93%
“…Each of these cells buds off yeast-like sporidia and new infectious dikaryons are produced by conjugation of two cells of opposite mating types. M. violaceum has been studied as an experimental model species in genetics (reviewed in Garber and Ruddat, 2002), host-race differentiation (eg Biere and Honders, 1996;Shykoff et al, 1999;Bucheli et al, 2000), and sex-ratio distortion (Kaltz and Shykoff, 1997;Oudemans et al, 1998;Hood and Antonovics, 2000;Thomas et al, 2003). M. violaceum has also been the basis for theoretical models on transmission dynamics (eg Thrall et al, 1993;Antonovics et al, 1994Antonovics et al, , 1995Thrall and Antonovics, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some populations are infected by the anther smut fungus Microbotryum violaceum, which may systemically infect plants and sterilize flowers and thus may have profound effects on plant fitness. The Silene-Microbotryum plant-pathogen system is one of the best studied plant-pathogen systems in natural populations (e.g., Antonovics et al 1994, Alexander and Antonovics 1995, Biere and Honders 1996, Shykoff and Kaltz 1997, Bucheli et al 2001). In the field, larger populations of Silene alba were more likely to be diseased than smaller populations (Antonovics et al 1994), and among our sampling populations we observed a similar trend (Galeuchet 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Under natural conditions, passive transmission of spores by wind or rain and infection of plants at the vegetative stage is a possible, but relatively rare option occurring only over short distances (Roche et al 1995). Inoculation of plants at the seedling or rosette stage has been widely used to investigate variation in resistance or infectivity (e.g., Baird and Garber 1979;Alexander 1989;Biere and Honders 1996;Shykoff and Kaltz 1997), and plant crosses more resistant to artificial inoculation are also more resistant when exposed to spores by insect transmission in the field (Alexander et al 1993).…”
Section: Study Organismsmentioning
confidence: 99%